Effect of single-layer versus two-layer gastric suture in epithelialization and pressure bursting in rats - Souza, Jeovana Pinheiro Fernandes; Freire, Juliana Mendonça; Celani, Lívia Medeiros Soares; Moreira, Marília Daniela Ferreira de Carvalho; Araujo-filho, Irami; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2018)
Purpose: To compare two techniques of suture on the stomach wall. Single-layer and two-layer of gastric suture were compared, evaluating: evolution of the epithelialization process in the gastric mucosa; tensile strength and histopathological changes in the suture area. Methods: Twelve (12) Wistar rats weighing 220 ± 18g were used. Group 1 (n = 6) – Gastric incision was sutured with single interrupted sutures in extramucosal single-layer; group 2 rats (n = 6) had the stomach incision sutured in two-layer technique. 6-0 polypropylene thread with atraumatic needle was used. On the seventh postoperative day the animals were anesthetized again to evaluate the tensile strength of the gastric sutures. The stomach healing sutured wound was removed, fixed in 10% formalin, for histopathological examination using H-E stain. Results: All animals survived the experiments. In the single-layer group pressure supported by the suture line was 247±30.2 mmHg. Compared with the pressure in the two-layer suture group (187.8 ± 25.5 mmHg), the difference was statistically significant (p<0.05). In the single-layer suture group, the aspect of the epithelium in the suture area showed awell-structured epithelium, perfect seal, small inflammatory reaction and normal healing compatible within the expected for the 7th postoperative day. In the two-layer suture group we observed an intense inflammatory reaction, and low epithelial regeneration in the suture zone. Conclusion: In conclusion, extramucosal single-plane gastric suture in rats supported higher intragastric pressure than in two-layer suture, and positively influenced the epithelialization on the suture zone.